'Black Bob'. (29th December 2018) - Wilmer, Val
Abstract : Bob Barclay (1911-1987) was the tuba player and leader of the Yorkshire Jazz Band and one of the few black musicians in the British revivalist (trad) scene of the 1950s and 1960s. The article describes the career of the YJB through interviews with its members, their associates and contemporary press coverage. It discusses the importance of Barclay's Studio 20 in Leeds as a meeting point for touring jazz musicians and other entertainers, both British and American. Barclay's situation as a person of colour on the jazz scene and in wider English society is considered.